Efficacy of atorvastatin in treatment of Iraqi obese patients with hypercholesterolemia - Farhan, Hassan A.; Khazaal, Faris A.; Mahmoud, Insaf J.; Haji, Ghazi F.; Alrubaie, Abdulhadi; Abdulraheem, Yousif; Almousawi, *, Ali M.; Alkuraishi, Mothanna (AL-Kindy College Medical Journal, 2014)
ABSTRACTBackground: dyslipidemia plays a crucial rule in the development of cardiovascular disease, which has become the leading cause of death in most developed countries as well as in developing countries (1). The effects of reducing low density lipoprotein – C (LDL-C) concentrations on the prevention of cardiovascular events and stroke have been well reported in many clinical trials.Objectives: Evidence supports the use of statins for lipid modifications in the primary prevention of coronary artery disease, morbidity and mortality. This study aims to determine the effectiveness of atorvastatin in treating dyslipidemia in Iraqi obese patients.Methods: 200 overweight and obese patients with hypercholesterolemia, according to NCEP ATP III criteria, were included. They were randomized into 3 groups according to atorvastatin dose, 10, 20, 40 mg/ day, and treated for 8 weeks. Blood lipid profile, liver enzymes ALT and AST, urea, creatinine, uric acid, calcium and glucose were measured before and after therapy.Results: There was a significant reduction of total cholesterol (TC), Triglycerides (TG), low density lipoprotein (LDL), very low density lipoprotein (VLDL), but a non-significant reduction of high density lipoprotein (HDL) with all atorvastatin doses. The high doses of the drug caused a significant elevation of serum levels of ALT and AST and a significant decrease of blood calcium; but there was nosignificant change in blood levels ofurea, creatinine, uric acid or glucose with any dose.Conclusion: Short-term atorvastatin therapy in dyslipidemic obese patients caused a reduction of TC, TG, LDL, and VLDL, but had no significant effect on HDL, non-significant changes in blood urea, serum creatinine, serum uric acid or blood glucose, while there was a dose dependent elevation of ALT and AST